Effect of multi-purpose tree species on chemical properties of an acid Alfisol in Meghalaya
A field investigation was initiated in 1987 at Barapani on an extremely P-deficient acid Alfisol to evaluate the multi-purpose tree species suitable for agro-forestry systems. Out of the 15 tree species studied, albizia [Periserianthesfalcataria(L.) Nielsen. syn Albizia molucama Miq.] indian alder (Alnus nepalensis D. Don), tree bean (Parkia roxburghiiG. Don) and champak(Michelia oblonga Wall. ex Hook. f. & Thoms.) were found promising for growth performance and timber volume. Different tree species intercropped with soybean [Glycine max(L.) Merr.